Optical Coherence Tomography Findings in Infectious Posterior Uveitis. (3rd April 2022) - Pichi, Francesco; Curi, André Luiz Land; Vasconcelos-Santos, Daniel Vitor; Marchese, Alessandro; Cicinelli, Maria Vittoria; Miserocchi, Elisabetta; Schlaen, Ariel
ABSTRACT: Purpose: To describe and illustrate the main optical coherence tomography (OCT) findings of infectious uveitis. Methods: Narrative review. Results: Posterior segment OCT in patients with infectious uveitis reveals posterior hyaloid face precipitates, superficial retinal precipitates and infiltrates, foveolitis, retinitis, neuro-retinitis, choroidal granulomas, and choroiditis as main imaging biomarkers. Some of these features are specific to the underlying causing etiology and may support the diagnosis and the initiation of treatment. Some OCT features disappear completely with resolution; some others are associated with irreversible retinal damage. Conclusions: OCT identifies different features of infectious uveitis into the vitreous, the retina, and the choroid. OCT characteristics, combined with other multimodal imaging features, are helpful in the differential diagnosis of infectious uveitis, the early detection of complications, and the assessment of the response to therapy.